Johann Friedrich Blumenbach Bibliographie seiner Schriften - Kroke, Claudia (Universitätsverlag Göttingen, 2010)
This bibliography documents the printed works of Johann Friedrich Blumenbach (1752-1840) and makes them accessible for research purposes. Blumenbach was Professor of Medicine and Natural History at the University of Göttingen. He was one of the leading exponents of the revolutionary change of the geo-biological concept of the world at the turn of the 18th to the 19th century. His works exemplarily show the interactions between the life sciences, the humanities and the social sciences of his day.